Sistem Sistem Pendukung Keputusan Pemilihan Karyawan Terbaik Dengan Metode AHP Pada PT Telkom Witel Kalbar: Sistem Pendukung Keputusan, Pemilihan Karyawan Terbaik, Metode AHP - Wira Prasetyo; Eni Heni Hermaliani; Riyan Latifahul Hasanah (Computer Science (CO-SCIENCE), 2023)
PT.Telkom Witel Kalbar currently has many employees but with so many employees, the selection of the best employees is done manually so that the company is still difficult to determine the best employees. With these problems, researchers are interested in conducting research in the form of a decision support system that can later help from the company to determine the selection of the best employees in the form of a application. The Analytical Hierarchy Process (AHP) is a theory that contains measurements used to find the ratio scale by means of pairwise comparisons between factors. This study uses the Analytical Hierarchy Process method as an alternative solution to the decision support system for selecting the best employees at PT. Telkom Witel Kalbar. The application of the AHP method is considered capable of providing an initial value of subjective problems and then becoming objective so as to increase the level of accuracy in selecting the best employees so as to get the results of the research, namely Mr. Satria became the best employee.